A biodegradable antibiotic-impregnated scaffold to prevent osteomyelitis in a contaminated in vivo bone defect model - McLaren, Jane S.; White, L.J.; Cox, H.C.; Ashraf, Waheed; Rahman, C.V.; Blunn, G.W.; Goodship, A.E.; Quirk, R.A.; Shakesheff, Kevin M.; Bayston, Roger; Scammell, Brigitte E. (AO Foundation, 2014)
Open fractures are at risk of serious infection and, if infected, require several surgical interventions and courses of systemic antibiotics. We investigated a new injectable formulation that simultaneously hardens in vivo to form a porous scaffold for bone repair and delivers antibiotics at high concentrations to the local site of infection. Duration of antimicrobial activity against Staphylococcus aureus was determined using the serial plate transfer test. Ultimate compressive strength and porosity of the material was measured with and without antibiotics. The material was evaluated in vivo in an ovine medial femoral condyle defect model contaminated with S. aureus. Sheep were sacrificed at either 2 or 13 weeks and the defect and surrounding bone assessed using micro-computed tomography and histology. Antimicrobial activity in vitro persisted for 19-21 days. Sheep with antibiotic-free material and bacteria became infected, while those with antibiotic-containing material and bacteria did not. Similarly, new bone growth was seen in uninoculated animals with plain polymer, and in those with antibiotic polymer with bacteria, but not in sheep with plain polymer and bacteria. The antibiotic-impregnated scaffolds were effective in preventing S. aureus infections whilst supporting bone growth and repair. If translated into clinical practice, this approach might reduce the need for systemic antibiotics.